The University Gender Gap in Australia: A Long-Run Perspective - Booth, A; Kee, H.J. (My University, 2009)
According to the 1911 Census, the proportion female of those receiving university education was around 22%, growing to 29% in 1921. By 1952 it had dropped to under 20%, due to easy access into universities for returning war-veterans. From the early 1950s, the university-educated gender gap began to reduce in response to women’s changing expectations of labour-force participation, fertility and age at first marriage. By 1987, Australian women were more likely than men to be enrolled at university. However, these aggregate figures disguise considerable heterogeneity across fields of study.
Centre for Economic Policy Research, the Australian National University, Discussion Paper
Keywords: Gender; Education and Training -- Tertiary; Gender -- Female; Education and Training; Learning, education and training; Gender; Gender; Education and Training; Tertiary; Female; Gender; Learning, education and training